2005
DOI: 10.1111/j.1472-9296.2005.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Innovation, Human Resource Management and Labour Market Structure: A Comparison of the EU-15

Abstract: We express our gratitude to the European Foundation for the Improvement of Living and Working Conditions for allowing us to use the results of the Third European Working Conditions Survey. We also thank the DARES, Ministry of Employment, France, for providing financial support for the research upon which this paper is based. We especially thank Alice Lam, Michel Gollac, Bengt-Aake Lundvall, Paul Nightingale and the editors of the JIR for their useful comments on previous versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 18 publications
10
97
0
8
Order By: Relevance
“…Increasing the organizing tasks of employees and their opportunities to use and develop their professional skills has the strongest relation with employee innovativeness. This is in line with the insights of Lorenz & Valeyre (2005) who differentiated between 'lean organizations' and 'learning organizations'. In both, employees had high levels of autonomy, yet this is combined in the lean organization with monotonous and repetitive jobs which, according to our findings, serve as an obstacle to employee innovativeness for white-collar workers.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increasing the organizing tasks of employees and their opportunities to use and develop their professional skills has the strongest relation with employee innovativeness. This is in line with the insights of Lorenz & Valeyre (2005) who differentiated between 'lean organizations' and 'learning organizations'. In both, employees had high levels of autonomy, yet this is combined in the lean organization with monotonous and repetitive jobs which, according to our findings, serve as an obstacle to employee innovativeness for white-collar workers.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
“…One of the predicted outcomes of the introduction of HPWS is an organization that flexibly responds to new environments. Lorenz & Valeyre (2005) characterized this model as an organization with high levels of employee autonomy, task complexity, learning and problem-solving. Assumingly, such 'learning type' organizations stimulate and enable their employees to be innovative and flexible.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Europe, Lorenz and Valeyre (2005) reported that one third of workers had jobs that were deskilled or that involved excessive demands. Significant technological and societal change is also affecting work and organizing, yet we know little about how this change might affect people's work design (Parker, 2014).…”
Section: A Synthesis Of Multi-level Factors That Affect the Design Ofmentioning
confidence: 99%
“…In fact, relatively few studies have directly assessed the influence of national employment policies on work design, although there is some supporting evidence. For example, relative to other countries, European countries with strict employment protection legislation have a higher proportion of high quality work designs (Lorenz & Valeyre, 2005) and are less susceptible to declines in cognitive demand (Eurofound, 2015).…”
Section: National Institutionsmentioning
confidence: 99%
“…Standardized work tasks and clear feedback might enable participation, but too strict standardization and goal-setting may also stifle innovative learning (Adler & Borys, 1996;Ellström, 2001). In organizations working with lean production, participation in decision making, employee involvement and opportunities for learning and reflection can be reduced by high performance pressure, precise standards and intensified work pace and demands (Landsbergis, 1999;Parker, 2003;Sprigg & Jackson 2006;Lorenz & Valeyre, 2005).…”
Section: Innovative Learning Climate and Collective Dispersion Of Ideasmentioning
confidence: 99%